Enhancement of interfacial strength of overmolded hybrid structures of short fiber reinforced polyamide 6 on continuous fiber reinforced epoxy composites under various surface pretreatments. Issue 2 (30th November 2021) - Ding, Yudong; Tang, Huaping; Shi, Wuping; He, Qingzhu; Zhai, Zhanyu
Abstract: Hybrid thermoset‐thermoplastic composites were fabricated by injection overmolding technique in this paper. To improve the interfacial bonding between short fiber reinforced polyamide 6 and continuous fiber reinforced epoxy composites, three different surface pretreatment methods (i.e., surface silanization, plasma treatment and CO2 laser ablation) were employed. The results show that surface silanization leads to a weak increase in polar functional groups of thermoset composites surface, resulting in a weak increase in interfacial bonding strength of overmolded composites. Compared with plasma pretreatment, CO2 laser ablation can achieve a highest shear bonding strength due to the formation of interface between injected melt polymer and carbon fibers. This kind of structure is favorable for the bonding strength due to mechanical interlocking. CO2 laser ablation is a promising technology to improve the bonding strength between short fiber reinforced polyamide 6 and continuous fiber reinforced epoxy composites. Abstract : Pretreatment, overmolding and evaluation of hybrid thermoset‐thermoplastic composites